An Aqueous Facile Synthesis of 2,3-Dihydroquinazolin-4(1H)-One Derivatives by Reverse Zinc Oxide Micelles as Nanoreactor - Mou, Jie; Chen, Ninghai; Zhao, Yu; Qi, Hao; Meng, Sihan; Xiang, Rui; Pei, Dongsheng (Frontiers in Chemistry, 2020)
A green synthetic protocol has been developed for the efficient preparation of 2,3-dihydroquinazolin−4(1H)-one derivatives with excellent yield in aqueous media. Reverse zinc oxide micelles catalyzed the reactions efficiently and selectively as the hallow nanoreactor. Moreover, the catalyst was reusable without significant loss of catalytic efficiency. The notable advantages of the procedure are high yields and mild reaction conditions, simple operation, nonchromatographic purification, environmentally friendly and good versatile substrates.